Chukchi traditional clothing as historical source of cultural transformation - Vukvukai, Nadezhda (Études/Inuit/Studies, 2007)
AbstractThis research note is based on the study of the Chukchi traditional clothing as a leading aspect of the national and cultural heritage of Chukotka. The topic was chosen by the need to show the advantages of Chukchi traditional clothing in the Arctic zone. Our scientific task was to collect data about Chukchi clothing and descriptions about its crafting in order to develop a method for professional training in their making and to promote this traditional knowledge.